Important value index (IVI) and diversity of mangrove vegetation in Aceh Tamiang, Aceh Province - Dewiyanti, Irma; Rifki, Muhammad; Octavina, Chitra; Ulfa, Maria; Damora, Adrian; Nurfadillah, Nurfadillah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Mangrove ecosystem is one of the unique ecosystems that has high productivity and it grows along the coast of Aceh Province, Indonesia. The mangrove vegetation in Aceh Tamiang District was decreasing due to human exploitation i.e. stems of mangrove vegetation utilized by local communities become charcoal and firewood. These activities have a negative impact on live and growth of mangrove vegetation. Therefore, the purposes of the study are to analyses the important value index (IVI), mangrove species diversity, and to analyses the correlation between substrate characteristics with mangrove density. The research stations determined using the purposive sampling method and each station has three plots as replication. There were 4 research stations located in Seruway, Bandahara, Banda Mulia, and Manyak Paye sub districts. The study reported 12 species of mangrove in the trees category, 9 species of saplings, and 8 species of seedlings. The 12 species of mangroves found were Avicennia lanata, A. marina, A. officinalis, Brugeira parviflora, B. sexangula, Ceriops decandra, C. tegal, Lumnitzera recomosa, Nypa fruticans, Rhizopora apiculata, R. stylosa, and Sonneratia alba. The R. apiculata was species commonly found in each sampling location and it had highest IVI for the tree, sapling and seedling categories with the value of 207.24, 300, and 200, respectively. The average of diversity index was 1.56 categorized in the medium category. The moment Pearson correlation showed there was no significant correlation between the physical-chemical water parameters and substrate with the density of mangrove where Psig0.05.Keywords:Mangrove vegetationImportant value indexDensityDiversityAceh Tamiang